what is the y-intercept of y=2(x+3)(x-4) it is-24 but why dont you multiply 2*-4

Guest Apr 26, 2019

#1**-3 **

You are not suppsed to multiply out this problem, this looks like a quadratic intercept form.

quadratic intercept form: y=a(x-p)(x-q)

a = vertical shift/stretch

p = root/x-intercept

q = root/other x-int

doorknoob Apr 26, 2019

#2**+1 **

when this eqaution intercepts the y-axis ....the 'x' value is = 0

put x = 0 in to the equation

y-intercept = 2(0+3)(0-4) = -24

ElectricPavlov Apr 26, 2019